ATRIBUTOS DA PAISAGEM RODOVIÁRIA AO LONGO DE UM GRADIENTE NATURAL-RURAL-URBANO NO BIOMA MATA ATLÂNTICA - MORAES, EMIDIO NEVES DE (2023)
Contact with nature is fundamental for people, a need felt mainly by city dwellers, as they have less access and live in highly anthropized landscapes. Therefore, taking advantage of alternatives for people's contact with nature is necessary - such as highways, as long as their visual, environmental, ecosystemic, and safety qualities are ensured, and thus begin to be perceived positively for the enjoyment of environmental and cultural benefits. This research aimed to characterize visual and environmental attributes, tree diversity and carbon stock, and road landscape safety to investigate their variation along a natural-rural-urban gradient. Hence, the SC-418 Highway and its right-of-way were selected as the study area. Visual quality was assessed using 272 photographs taken every km of the highway, in both directions (East-West and West-East) and two data collection periods (winter and summer), considering its variation in natural, rural, and urban areas. Naturalness, predominant form of plant life, diversity of vegetation strata and vegetation colors, diversity of landscape elements, relief class, and intervisibility were analyzed to compose a Road Landscape Visual Quality Index (IQVPR). Environmental quality, in turn, was assessed in a Geographic Information System (GIS) environment using the normalized difference vegetation index (NDVI), land use and land cover, and landscape metrics of area, shape, and distance between fragments, to compose a Road Landscape Environmental Quality Index (IQAPR). Furthermore, a forest inventory was carried out through systematic sampling stratified on the natural-rural-urban gradient to collect variables for calculating tree diversity and carbon stock, and to evaluate tree risk through visual analysis to assess landscape safety. The results indicate that urban areas have lower visual and environmental indexes (IQVPR and IQAPR), the presence of exotic species, lower tree diversity (but greater carbon stock), and more structural defects in trees – and, therefore, more risk factors. In conclusion, SC-418 Highway should be considered a Parkway in its natural gradient, and the planning, management, planting, and maintenance of native species trees is recommended in its urban gradient, so that the highway may be an alternative for contact between people and nature throughout its entirety.